2018
DOI: 10.1093/mnras/sty2747
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Milky Way as a dry Galaxy

Abstract: We construct a model for the Milky Way Galaxy composed of a stellar disc and bulge embedded in a dark-matter halo. All components are modelled as N -body systems with up to 8 billion equal-mass particles and integrated up to an age of 10 Gyr. We find that net angular-momentum of the dark-matter halo with a spin parameter of λ = 0.06 is required to form a relatively short bar (∼ 4 kpc) with a high pattern speed (40-50 km s −1 ). By comparing our model with observations of the Milky Way Galaxy, we conclude that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 68 publications
11
75
0
Order By: Relevance
“…Interestingly, Asano et al (2020) found higher-order bar resonance features in the self-consistent MW simulation by Fujii et al (2019) that might resemble the velocity structure of the 'Hercules' sub-arches. Their 'Hercules 2', 'Hercules 1', and 'Horn' arches would in this case be associated with 1:5, 1:4, and 1:3 bar resonances.…”
Section: Higher-order Resonances: a Curious Coincidence In Thementioning
confidence: 96%
“…Interestingly, Asano et al (2020) found higher-order bar resonance features in the self-consistent MW simulation by Fujii et al (2019) that might resemble the velocity structure of the 'Hercules' sub-arches. Their 'Hercules 2', 'Hercules 1', and 'Horn' arches would in this case be associated with 1:5, 1:4, and 1:3 bar resonances.…”
Section: Higher-order Resonances: a Curious Coincidence In Thementioning
confidence: 96%
“…While we still cannot match the resolution of the Gaia data, we can easily pick out several moving groups when selecting regions on the kpc or less scale at the Solar radius. For example, Fujii et al (2019) have previously used Bonsai simulations to examine the vR − v φ plane around the Outer Lindblad Resonance (OLR) of a short fast bar. Similar to previous studies (e.g.…”
Section: Model M1: Planar Dynamics and The Classical Moving Groupsmentioning
confidence: 99%
“…In order to resolve substructures in the phase-space, we used 120 × 10 6 particles to model the stellar disk component and 61451200 particles to model the dark matter halo, making this model one of the highest resolution N-body simulations of an isolated disk galaxy (see, e.g., Fujii et al 2019;Khoperskov et al 2019;Asano et al 2020). Note however, that the number of particles in a SNd-like region in this high-resolution model is still by a factor of ∼ 5 lower than the number of stars already available in the Gaia RVS sample.…”
Section: Model Descriptionmentioning
confidence: 99%